SureMsg: a XMPP-based security e-mail system. (21st August 2007) - Bi, Jun; Wu, Jianping; Zhang, Wenmao
The Internet e-mail service based on SMTP protocol is an important information infrastructure. Meanwhile, the instant messaging becomes an emerging Internet application. This paper presents a security e-mail system based on instant messaging protocol to resolve the problem of SPAM. After introducing the design of architecture, client system and server system, this paper presents the security and reputation mechanism. To support the incremental deployment, this paper also discusses the interoperation between XMPP based e-mail system and SMTP based system, and presents the solution for transition from current e-mail system to the new system.